Evaluasi Efektivitas Manajemen dan Rekayasa Lalu Lintas Pada Simpang Asemka Dalam Rangka Mendukung Kebijakan Low Emission Zone Kota Tua Jakarta Barat - Subastian, Djamal; Suryobuwono, Abdullah Ade; Agustin, Arneta (Institut Transportasi dan Logistik Trisakti, 2022)
The Low Emission Zone policy in the Kota Tua tourist area is carried out by carrying out traffic engineering at the Asemka intersection which is the meeting place of Jl. Pintu Besar Selatan (south approach), Jl. Pintu Besar Utara- Jl. St. Kota (north approach), Jl. Jembatan Batu (east approach), and Jl. Fly Over Pasar Pagi and Jl. Asemka (western approach). After the implementation of traffic engineering, it is necessary to analyze how the performance of the intersection is to determine the impact of diverting traffic flow from several roads. The method used in this study is MKJI 1997 to determine the performance of road sections manually and PTV Vissim which is a microsimulation software to determine the performance of intersections, from both methods the parameters obtained from the research results are almost close. From the analysis results obtained speed 54.81 km/hour, delay 72.11 seconds, the vehicle stopped 2.7 seconds/pcu with level of service F, from the simulation results obtained speed 53.25 km/hour, delay 37.26 seconds, vehicle stopped 1.43 seconds/pcu with level of service D, the difference from the calculation results is below 5% with the information received.